Analytical Study of skill and some correction factors influencing the Duhok Sports Club basketball team first place winner in the Iraqi Premier League season 2013 - 2014 - Zayaa Hurmiz, Samira (Journal of Physical Education, 2015)
The aim of this research is to detect the effect of environments factors such spectators, court, traveling and residency on the results of the skill of shooting (free throw, two points throw, three points throw) between the matches that be held on the court of Duhok club and the matches that be held on the courts of other clubs. Also, to know the percentage and the means of the successful of the three kind shoots from the total of successful and fall shoots. Finally, to know the percentage and the mean of the successful shoots from the successful and fall shoots to each player according to his participating time. The theoretical side of the research includes the analysis and evaluating in sport field, skill of shooting, kinds of shooting, and factors that help to develop this skill. The procedures of this research includes, the sample of the research that representing thirteen players who participate in variety times in the matches according to their skill s. The discussion of the results build up according to the purposes of this research. The researcher found out that the players of Duhok club don't be effected whether the match's hold on the court of Duhok club or on the courts of other clubs. Also, the players of this club characterized by having the highest score in the free shoot comparing with the shoots of tow points and three points. Finally the results show that, the professional experiment of Duhok club was very successful, especially with the players of foreign countries or with the Iraqi players from the Iraq varsity while there was a weak chose to local players from the region of Kurdistan The researcher submits a number of recommendations proper to the aims of the research